A Conceptual Approach To Evaluating The Political Economics Of Mining In Africa And The Sector?s Contribution To Economic Diversification ? Synopsis - M. H. Solomon (The Southern African Institute of Mining and Metallurgy, 2011)
After the global financial crisis of 2008, African mining is entering anew phase of development. The rapid withdrawal of emerging market funding from the critical exploration and development industries provided a hiatus in funding, a gap which was quickly filled by Chinese and other Asian investors. While the continent is still economically dependent on its extractive industries, the prevalence of Dutch Disease has undermined Africa?s ability to benefit fully from its mining, oil, and gas industries. While the extractive industries are closely related to many of the more fragile and failed states in Africa, it is equally true that the strongest states in Africa have mining-based economies. This paper explores the possible linkages between mining, strong and weak political economies, and poverty in Africa. It draws the conclusion that neither Dutch Disease nor Resource Course is a given in resource-endowed countries, and that it can be avoided if the mining economies in these countries are actively integrated into their respective broader economies and used to foster economic diversification. The author asserts that given the capacity constraints of many African governments, it is contingent on mining companies to become integrally involved in catalysing diversification around their infrastructure and supply chains.